chillers spooked - Wooderson, Philip (London A&C black Ltd, 1994)
"Spooked," a title in the Chillers children's horror series by Philip Wooderson (1996), follows a boy named Pete who finds a desperate "Please help me" note from a girl named Lisa inside a locked drawer in an old chest. Driven to uncover the mystery, Pete explores a creepy, abandoned house during Halloween, turning his investigation into a frightening experience.
English